2022
DOI: 10.3390/en15082944
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of a Thermoelectric Generator with Hybridization of Segmented Materials and Irregularly Variable Cross-Section Design

Abstract: As a direct energy converter between heat and electricity, thermoelectric generators (TEGs) have potential applications including recovery of waste heat, and solar thermoelectric power generation. Geometric parameter and material are two critical factors to improve the TEG performance. However, the strategies base on structure design and material development are always separated. There are limited studies on the effects of consolidating them simultaneously. Here, an idea of segmented material coupled with irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The authors also proposed that 2n-1p segmentation is the best performing in terms of power and conversion efficiency. Zhang et al [194] optimized the geometry of a segmented TEG with an irregularly variable cross-section design, utilizing a genetic algorithm. They determined that only segmentation or a variable cross-section design could achieve the optimum design for a fixed thermoelectric material volume.…”
Section: Segmented Leg Geometrymentioning
confidence: 99%
“…The authors also proposed that 2n-1p segmentation is the best performing in terms of power and conversion efficiency. Zhang et al [194] optimized the geometry of a segmented TEG with an irregularly variable cross-section design, utilizing a genetic algorithm. They determined that only segmentation or a variable cross-section design could achieve the optimum design for a fixed thermoelectric material volume.…”
Section: Segmented Leg Geometrymentioning
confidence: 99%
“…The internal resistance of Bismuth Telluride and modified Lead Telluride (p-n type) shown in Figure 1 and Figure 2 can be written by the Eqs. ( 16) - (18); )}…”
Section: Performance Of Segmented Tegsmentioning
confidence: 99%
“…While the heat on the cold side is losing by natural convection. Design [18], Compare the performance of TEGs was performed, with a rectangular leg, segmented leg, and a variable cross-sectional leg to optimize the performance of TEG. The results showed that segmented TEG presented output power the highest than traditional TEG of about 51.71 %.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of recent literature evidences an ever increasing number of innovative technological approaches capable to improve the conversion efficiency of radioscope thermoelectric batteries and to allow a miniaturization of the devices. Due to the multiple physical processes involved in the conversion of heat in electricity, there are several ways of addressing such a demanding task 41 . However, it has been highlighted that the greatest effects on the performances of a RTG are produced by the design and the materials of the legs.…”
Section: Basic Concepts and Conversion Mechanismsmentioning
confidence: 99%
“…Due to the multiple physical processes involved in the conversion of heat in electricity, there are several ways of addressing such a demanding task. 41 However, it has been highlighted that the greatest effects on the performances of a RTG are produced by the design and the materials of the legs. Consequently the development of precise structural arrangements and the exploration of new thermoelectric materials have been the main objective of recent researches, that generated the aforementioned "proof-of-concept."…”
Section: Static Conversion Systemsmentioning
confidence: 99%